2007
DOI: 10.1017/s0007114507691806
|View full text |Cite
|
Sign up to set email alerts
|

Food security status in households of people living with HIV/AIDS (PLWHA) in a Ugandan urban setting

Abstract: Because HIV/AIDS negatively impacts on the food security status of households, it is crucial to identify how households respond to these impacts, in order to identify positive food security entry points and design strategies that can effectively alleviate food insecurity among the households of people living with HIV/AIDS (PLWHA). A cross-sectional study was thus undertaken to establish how HIV affected households in an urban Ugandan setting in terms of response to food shortages and the interrelations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
106
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 5 publications
12
106
2
2
Order By: Relevance
“…Reduced food intake in HIV affected households could also be secondary to loss of income and food production capacity in the family due to labor loss, psychosocial factors, or medication sideeffects [4][5][6]. Like other chronic care drugs antiretroviral drugs are difficult to take on an empty stomach due to associated side effects, distance from health facility and transportation cost, search of work add additional burden on a patient with impaired immunity influences retention on HIV/AIDS treatment and care [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced food intake in HIV affected households could also be secondary to loss of income and food production capacity in the family due to labor loss, psychosocial factors, or medication sideeffects [4][5][6]. Like other chronic care drugs antiretroviral drugs are difficult to take on an empty stomach due to associated side effects, distance from health facility and transportation cost, search of work add additional burden on a patient with impaired immunity influences retention on HIV/AIDS treatment and care [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity, leads to increased risk of HIV transmission and rapid disease progression [41]. The effect Food insecurity on adherence to HAART globally is multifactorial and different studies reported that lower levels of medication adherence among food insecure individuals taking HAART [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these types of food consumption measures range in scope from the commonly used 98-food items Block FFQ [67] to quick categorizations based on consumption of seven culturally-based food groups [68]. In an international context, modified version of this type of questionnaire has been used by some organizations and researchers [25,68].…”
Section: Dietary Diversity Measuresmentioning
confidence: 99%
“…Perhaps most notable, several studies have used the HDDS [25] or an adapted HDDS to measure dietary quality among HIV-positive people in Ethiopia [76], Malawi [77] and Uganda [68]. The HDDS is used widely programmatically and typically measures dietary diversity at household level.…”
Section: Dietary Diversity Measuresmentioning
confidence: 99%
See 1 more Smart Citation